The Effects Of Job Crafting On Task Performance : The Mediating Role Of Work Engagement And Employee Creativity - Yuyun Mulyati; Asep Hermawan; Sarfilianty Anggiani (CV. AFDIFAL MAJU BERKAH, 2024)
This research aims to determine the role of work engagement and employee creativity in mediating the influence of job crafting on task performance in the Bapenda of West Java Province. Data was collected using a questionnaire distributed online to employees at CPPD Bapenda offices in five regions in West Java. A total of 267 respondents participated in filling out the questionnaire, which was distributed via Google Form by selecting samples using proportionate stratified random sampling, and then the data was processed using the structural equation modelling (SEM) approach with the partial least squares (PLS) method. The research results found that job crafting does not have a positive effect on task performance, but it needs a mediating role in work engagement. The role of employee creativity arises when work engagement exists as a variable that mediates the influence of job crafting on employee creativity, and work engagement acts as a variable that encourages employee creativity as a variable that mediates its influence on task performance. Future research is expected to expand testing on variables that encourage job crafting to influence employee creativity and task performance. Apart from that, it is necessary to examine other variables that influence task performance in other public and private sectors.